Regulatory Mechanism of ITGBL1 in the Metastasis of Colorectal Cancer - Qi, Lu; Song, Fuyao; Ding, Yanqing (Frontiers in Oncology, 2020)
Integrin, beta-like 1 (ITGBL1) protein is located in the extracellular matrix (ECM) and involved in the development and metastasis of many tumors. However, the regulatory mechanism of ITGBL1 in colorectal cancer (CRC) remains unclear. This study was to analyze the expression profile of CRC and to identify the expression change of ITGBL1 gene at different stages of CRC. Survival analysis showed that ITGBL1 was related to the metastasis of CRC, and CRC patients with a high expression of ITGBL1 had earlier metastasis. Gene Set Enrichment Analysis (GSEA) indicated the relationship between ITGBL1 expression and molecular events of CRC. The results indicated that a high expression of ITGBL1 was linked to Wnt signaling pathway, cell polarity, and tissue development, while a low expression of ITGBL1 was related to cellular respiration, electron transfer chain, and oxidative phosphorylation. With the expression profiles from interstitial and parenchyma CRC tissues, a comparison was made to determine the difference between high/low expression of ITGBL1 and Wnt signaling pathway, respectively, and further confirmed the close relation between ITGBL1 and Wnt signaling pathway. To determine the relation, an interaction network of ITGBL1 and Wnt signaling proteins was constructed. It was found that β-catenin interacted with multiple extracellular Wnt signals and could bind to ITGBL1. As a result, the regulatory mechanism of ITGBL1 in CRC is related to extracellular Wnt signals and may affect extracellular Wnt signals via β-catenin.